2019
DOI: 10.1021/jacs.9b03850
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Directed Lewis-Acid Catalysis for Peptide Synthesis

Abstract: A Lewis-acid-catalyzed method for the substrate-directed formation of peptide bonds has been developed, and this powerful approach is utilized for the new "remote" activation of carboxyl groups under solvent-free conditions. The presented method has the following advantages: (1) the high-yielding peptide synthesis uses a tantalum catalyst for any amino acids; (2) the reaction proceeds without any racemization; (3) the new substrate-directed chemical ligation using the titanium catalyst is applicable to converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…This work was further developed with a tantalum variant of the original catalyst, Ta(OMe) 5 that could exploit the same bidentate chelation mode (Figure 16, 64) to facilitate amidation of an ester, but this variant employed a carbamate as the α-substituent. [121] The same investigators showed that Boc-protected amino acid esters could be directly amidated with free amino acid esters. They also reported that this effect could work "downstream," wherein Bocprotected dipeptide methyl esters could also be amidated (with the aid of bidentate or higher order ligands) to yield a tripeptide (Figure 17, 67 ing protected serine and threonine with amino acids.…”
Section: Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work was further developed with a tantalum variant of the original catalyst, Ta(OMe) 5 that could exploit the same bidentate chelation mode (Figure 16, 64) to facilitate amidation of an ester, but this variant employed a carbamate as the α-substituent. [121] The same investigators showed that Boc-protected amino acid esters could be directly amidated with free amino acid esters. They also reported that this effect could work "downstream," wherein Bocprotected dipeptide methyl esters could also be amidated (with the aid of bidentate or higher order ligands) to yield a tripeptide (Figure 17, 67 ing protected serine and threonine with amino acids.…”
Section: Metalsmentioning
confidence: 99%
“…Methyl Luo [127] La 2 Na 8 (OCH 2 CF 3 ) 14 (THF) 6 Neat 80 .5 Methyl Yao [128] Nb(OEt) 5 Neat 50-80 2-5 Methyl Yamamoto [120] Nb 2 O 5 Neat 140 50* Methyl Shimizu [119] Ni(cod) 2 Lx Toluene 60 15 Methyl Garg [23] Ni(cod) 2 Lx Toluene 140 10 Methyl Newman [115,116] Ni(Glyme)Cl 2 Lx NMP 120 7.5 Methyl Hu [117] Nitroarenes as amine source Pd(IPr)(allyl)Cl Toluene 110 3 Phenyl Newman [118] Ta(OEt) 5 Toluene 60-100 10 Methyl Yamamoto [122] Ta(OMe) 5 Neat or CHCl 3 or DMSO 40-70 10 Methyl Yamamoto [121] Use of TMSIM as additive lowers temp to 30-50 ZrCl 4 Toluene 90 5 Methyl Ghinet [123] ZrCp 2 Cl 2 Toluene 110 10 Methyl Mecinovic [124] 4.2.1 | Acceptorless oxidative amidation…”
Section: Thf 30 30mentioning
confidence: 99%
See 1 more Smart Citation
“…[104] Recently lewis acid is used as catalyst in substrate-directed peptide synthesis. [105] Yuan et al reported asymmetric alkylation using chiral lewis acid catalyst of inactivated δ-position of N-alkyl amides with 97% enantiomeric excess. [106] Insertion of thioketenes into donor-acceptor cyclopropanes under lewis acid catalysis condition was presented by Augustin, the reaction proceeds through formal [3+2]-cycloaddition and a subsequent [2+2]cycloreversion with release of dialkyl ketene (scheme 13).…”
Section: Lewis Acid As Catalystmentioning
confidence: 99%
“…Tellingly, our initial report of a boron‐based catalyst for the amidation between carboxylic acids and amines [6] and several catalytic amide bond formations and peptide syntheses have been reported [7] . Among them, we are interested in several investigations on catalytic peptide synthesis using Lewis acids such as niobium, [8] tantalum, [9] and boronic acid [10] . We envisioned Brønsted acid covalent bond formation where the effectiveness of Lewis acid catalysts has been confirmed in peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%